2006
DOI: 10.1111/j.1525-1438.2006.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

What is the difference between squamous cell carcinoma and adenocarcinoma of the cervix? A matched case–control study

Abstract: The objective of this study was to investigate the efficacy of treatment strategies in patients with adenocarcinoma (AC) of the cervix and compare it with those with squamous cell carcinoma (SCC) of the cervix. Women with FIGO (1994) stage IB1 AC, especially pathologic tumor size of 2-4 cm, treated with class III hysterectomy, were compared with those with SCC treated with comparable strategy in a case-controlled study. Eighty patients (20 cases, 60 controls) were analyzed. Lymphvascular space invasion (P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…Grisaru et al (2001) reported that 799 surgically treated patients with FIGO stage IA -IB disease of AC or SCC had a similar prognosis. Look et al (1996) and Lee et al (2006) reported same results in 749 and 60 patients with FIGO stage IB disease, respectively. A similar finding was noted in a study from Fregnani et al (2008), in which 238 FIGO stage IB -IIA patients with AC or SCC were assessed.…”
Section: Spread Pattern and Failure Sitessupporting
confidence: 69%
See 1 more Smart Citation
“…Grisaru et al (2001) reported that 799 surgically treated patients with FIGO stage IA -IB disease of AC or SCC had a similar prognosis. Look et al (1996) and Lee et al (2006) reported same results in 749 and 60 patients with FIGO stage IB disease, respectively. A similar finding was noted in a study from Fregnani et al (2008), in which 238 FIGO stage IB -IIA patients with AC or SCC were assessed.…”
Section: Spread Pattern and Failure Sitessupporting
confidence: 69%
“…In the reported literature, no differences were found in positive lymph node rates of FIGO stage IB disease, and positive rates were approximately 5 -15% (Look et al, 1996;Irie et al, 2000;Lee et al, 2006). Few reported literature have discussed lymph node status of advanced stage, that is, FIGO stage IIB.…”
Section: Spread Pattern and Failure Sitesmentioning
confidence: 87%
“…The prognosis of patients with AdCa after RH is unclear, primarily because studies have been performed on small numbers of patients. Some of these studies found that patients with AdCa have poorer prognosis than do those with SCCa (Hopkins and Morley, 1991;Eifel et al, 1995;Look et al, 1996;Samlal et al, 1997;Lai et al, 1999;Kim et al, 2000;Nakanishi et al, 2000), whereas other reports found no differences in prognosis (AntonCulver et al, 1992;Miller et al, 1993;Shingleton et al, 1995;Grisaru et al, 2001;Ayhan et al, 2004;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009). Therefore, the prognosis after RH and the optimal management of AdCa are still a subject of debate.…”
mentioning
confidence: 88%
“…Lee et al and other researchers have shown that patients with early-stage AC who are treated surgically have a very poor prognosis 8 . However, other investigators have been unable to find this difference in survival between distinct histologic types 12 .…”
Section: Introductionmentioning
confidence: 94%